Predicting potential distribution and identifying priority areas for conservation of the Yellow-tailed Woolly Monkey (Lagothrix flavicauda) in Peru - Guzman, Betty K.; Cotrina Sánchez, Alexander; Allauja Salazar, Elvis E.; Olivera Tarifeño, Christian M.; Ramos Sandoval, Jhonny D.; Hoyos Cerna, Marlon Y.; Barboza Castillo, Elgar; Torres Guzmán, Cristóbal; Oliva Cruz, Manuel (Urban und Fischer Verlag GmbH und Co. KG, 2022)
Species distribution models (SDMs) provide conservationist with spatial distributions estimations of priority species. Lagothrix flavicauda (Humboldt, 1812), commonly known as the Yellow-tailed Woolly Monkey, is one of the largest primates in the New World. This species is endemic to the montane forests of northern Peru, in the departments of Amazonas, San Martín, Huánuco, Junín, La Libertad, and Loreto at elevation from1,000 to 2,800 m. It is classified as “Critically Endangered” (CR) by the International Union for Conservation of Nature (IUCN) as well as by Peruvian legislation. Furthermore, it is listed in Appendix I of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). Research on precise estimates of its potential distribution are scare. Therefore, in this study we modeled the potential distribution area of this species in Peru, the model was generated using the MaxEnt algorithm, along with 80 georeferenced occurrence records and 28 environmental variables. The total distribution (high, moderate, and low) for L. flavicauda is 29,383.3 km2, having 3,480.7 km2 as high potential distribution. In effect, 22.64 % (6,648.49 km2) of the total distribution area of L. flavicauda is found within Natural Protected Areas (NPAs), with the following categories representing the largest areas of distribution: Protected Forests (1,620.41 km2), Regional Conservation Areas (1,976.79 km2), and Private Conservation Areas (1,166.55 km2). After comparing the predicted distribution with the current NPAs system, we identified new priority areas for the conservation of the species. We, therefore, believe that this study will contribute significantly to the conservation of L. flavicauda in Peru.